Manager characteristics and the informativeness of banks’ loan loss provisioning - Bischof, Jannis; Rudolf, Nicolas (Review of Accounting Studies, 2025)
This study investigates the role of individual managers in banks' financial reporting. We exploit the connectedness between different managers and find that individual bank managers explain approximately 19 percent of banks' loan loss provisions. This observation is consistent with the substantial reporting discretion that individual bank managers use in the estimation of loan loss provisions and that is increasingly subject to financial stability concerns by prudential supervisors. Our results suggest that these concerns are valid, as individual management discretion is associated with greater discretionary loan loss provisions and proxies for opportunistic accounting, especially the reduction in the timeliness of these provisions and the lesser degree to which the allowance for credit losses maps into future charge-offs. These findings are relevant for the design of regulatory measures aimed at limiting the managerial influence on accounting choices in banking and can inform debates on the desirability of discretion within the reporting process of banks.